2022
DOI: 10.3389/fonc.2022.911309
|View full text |Cite
|
Sign up to set email alerts
|

The Function, Role and Process of DDX58 in Heart Failure and Human Cancers

Abstract: BackgroundHeart failure (HF) is the most common outcome of cardiovascular disease, and an increasing number of patients with heart failure die from noncardiac causes, such as cancer. Epidemiological data suggest that ischemic cardiomyopathy–induced HF (ischemic HF) may be associated with an increased incidence of cancer. This study aimed to investigate the possible mechanisms of the association between ischemic HF and cancer, as well as potential therapeutic targets.MethodsWeighted gene co-expression network a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…Previous studies have shown that DDX58 is a proto-oncogene, an important immune-related gene closely related to immune cell in ltration, and its high expression might promote the occurrence of cancer [29]. Similarly, our results indicated that the expression of DDX58 in tumour samples was signi cantly higher than that in normal samples and boosted the number of monoclonal formations and cell viabilities in TNBC cells.…”
Section: Discussionsupporting
confidence: 76%
“…Previous studies have shown that DDX58 is a proto-oncogene, an important immune-related gene closely related to immune cell in ltration, and its high expression might promote the occurrence of cancer [29]. Similarly, our results indicated that the expression of DDX58 in tumour samples was signi cantly higher than that in normal samples and boosted the number of monoclonal formations and cell viabilities in TNBC cells.…”
Section: Discussionsupporting
confidence: 76%
“…Previous literature has disclosed that there are two prerequisites for satisfying response to immunotherapy, sufficient immune infiltration and abundant expression of immune checkpoint. 31,32 Therefore, screening immune characters through NAS-based scores lays the foundation for predicting response to immunotherapy. [33][34][35][36] To be noted, the transcriptomic data and qPCR assay revealed that S100A9 was rare in hepatoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the NAS‐activated subgroup was characterized by a significant infiltration of immune cells but increased expression of immune checkpoint‐related genes. Previous literature has disclosed that there are two prerequisites for satisfying response to immunotherapy, sufficient immune infiltration and abundant expression of immune checkpoint 31,32 . Therefore, screening immune characters through NAS‐based scores lays the foundation for predicting response to immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Altered expression of ATOH8 [364], STAT1 [365], ARG1 [366], TLR4 [367], VNN1 [368], ABCA1 [369], IFIH1 [370], PTGS2 [371], F2RL1 [289], CYP2D6 [372], PDK4 [373], RNF213 [374], JAK2 [375], NOTCH2 [376], PDGFC (platelet derived growth factor C) [377], TLR2 [378], CYP1B1 [379], IL1RN [380], GCH1 [381], EGR1 [382], HIF1A [383], PLA2G7 [384], CCR2 [385], GAB1 [386], VEGFA (vascular endothelial growth factor A) [387], OGT (O-linked N-acetylglucosamine (GlcNAc) transferase) [388], OXR1 [389], IRF9 [390], FMR1 [391], LDLR (low density lipoprotein receptor) [392], SIRT1 [393], NOD2 [394], ATP13A3 [395], VCAN (versican) [396], FGL2 [397], TET2 [398], KDM6A [399], KLHL2 [400], CAVIN1 [401], TNFRSF4 [402], PF4 [403], VEGFB (vascular endothelial growth factor B) [330], CCR7 [404], PRDX2 [405], HSPB1 [406], TCF4 [407], MRPL4 [408], PHF14 [409], TRPM4 [410], AQP3 [411] and LGMN (legumain) [412] were observed to be associated with the progression of hypertension. Recent studies have shown that altered expression of DDX58 [413], STAT1 [414], TLR4 [415], CYP2D6 [416], JAK2 [417], TLR2 [418], DUSP6 [419], HDAC9 [420], LATS2 [421], CA2 [150], HIPK3 [422], CCR2 [423], GAB1 [120], UFL1 [424], OGT (O-linked N-acetylglucosamine (GlcNAc) transferase) [425], PRKAR1A [265], SIRT1 [426], FGL2 [427], TET2 [428], ASCC2 [429], BIN1 [430], HSPB1 […”
Section: Discussionmentioning
confidence: 99%